Making immunology inclusive: a low-cost, high-impact activity for exploring T cell receptor diversity - Davis, Claudette P. (Frontiers in Education, 2025)
The function of the immune system is to protect and keep us safe. The immune system surveillance will protect us from foreign antigens entering our body and rogue cells that are no longer under cell cycle control. Considering the most recent pandemic, our students must understand how our immune system works and the function of essential cells involved in this system. However, due to curriculum constraints, particularly at the community college, it may not be feasible for non-biology majors or biology majors to experience the fascinating inner workings of the immune system. Undergraduate students enrolled in an introductory biology, immunology, or microbiology course may not fully grasp the magnitude of receptor diversity embedded in our T cells. The creation of an in-class activity highlights the T cell receptor and provides a deeper understanding of T cell receptor (TCR) diversity. Instructors can use the activity in a lecture or laboratory setting where students work in small groups and use clay to construct different TCRs. Students explore TCR diversity using an interactive V(D)J table of antigen codes. The activity sought to engage students in the classroom to reinforce how T cell diversity contributes to the receptor recognizing the many antigens our bodies encounter daily. The ASPECT (Assessing Student Perspective of Engagement in Class Tool) survey was used to determine students' level of collaboration within their group and their experience with the activity. Results show that students welcomed the activity and felt their contributions and actions during the activity promoted learning.